Vakfiyesi Işığında Şah Sultan ve Zal Mahmud Paşa Külliyesi - Kahraman, Betül (FSM Vakıf Üniversitesi)
Bu makalede Osmanlı medeniyetinin en önemli değerlerinden olan vakıflar’ın bir örneği olarak Şah Sultan ve Zal Mahmud Paşa Vakfı ele alınmıştır. 16. yüzyıl sonunda kurulan bu vakfın kurucuları II. Selim’in kızı Şah Sultan ile eşi Vezir Zal Mahmud Paşa’nın hayatı ve kurmuş oldukları vakıflar irdelenmiştir.

In this article, Şah Sultan and Zal Mahmud Pasha Charity was taken into consideration as an example of ‘‘Charities’’ which is one of the most important values of Ottoman Civilization. Life story of founders of charity who was the daughter of Selim II, Şah Sultan and her husband Vizier Zal Mahmud Pasha and information about their charities which where founded at the and of 16th Century, were stated.
In the Light of Its Vaqfiyye, Şah Sultan and Zal Mahmud Pasha Complex
Keywords: Vakfiye; Şah Sultan ve Zal Mahmud Paşa; Osmanlı vakıfları; Ottoman foundations; Vaqfiyye; Şah Sultan and Zal Mahmud Pasha